(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper addresses critically the incorporation of some ideas from Gadamer’shermeneutical philosophy into the ongoing disputes in Criminal Law Theory (in particular,in the field of legal interpretation).